Efficiency rate of independent floating water treatment device (IFWAD) - Zawawi M.H.; Zainal N.S.; Swee M.G.; Zahari N.M.; Kamarudin M.A.; Shabbir M.S. (American Institute of Physics Inc., 2023)
The independent Floating Treatment Device (IFWAD) is a small scale water treatment device specifically functions to treat water. The independent term being used due to IFWAD is not dependent to any power source as it receive it powers from solar. Additionally, its floating features enable it to being place anywhere according to the suitability of site condition. Treatment element of this device used absorption and adsorption capacity of the activated carbon to remove pollutants. Removal parameters used are turbidity, chemical oxygen demand, biological oxygen demand and suspended solid. The result shows about 94% removal efficiency for turbidity. TSS result showed about 92% of TSS removal after 48 hours of treatment. Chemical oxygen demand (high range) shows almost 0 for reading after 84 hours of treatment. The pH for water sample not exceed 8 and the temperature remain below 40 C. the color result showed decreasing in number from 1036 pt-co to 7.5pt-co after 48 hours of treatment. 2017 Author(s).